Autoradiography of 3H-pirenzepine and 3H-AFDX-384 in Mouse Brain Regions: Possible Insights into M1, M2, and M4 Muscarinic Receptors Distribution - Valuskova, Paulina; Farar, Vladimir; Forczek, Sandor; Krizova, Iva; Myslivecek, Jaromir (Frontiers in Pharmacology, 2018)
Autoradiography helps to determine the distribution and density of muscarinic receptor (MR) binding sites in the brain. However, it relies on the selectivity of radioligands towards their target. 3H-Pirenzepine is commonly believed to label predominantly M1MR, 3H-AFDX-384 is considered as M2MR selective ligand. Here we performed series of autoradiographies with 3H-AFDX-384 (2 nM), and 3H-pirenzepine (5 nM) in WT, M1KO, M2KO and M4KO mice to address the ligand selectivity. Labeling with 3H-pirenzepine using M1KO, M2KO and M4KO brain sections showed the high selectivity towards M1MR. Selectivity of 3H-AFDX-384 towards M2MR varies among brain regions and depends on individual MR subtype proportion. All binding sites in the medulla oblongata and pons, correspond to M2MR. In caudate putamen, nucleus accumbens and olfactory tubercle, 77.7%, 74.2% and 74.6% of 3H-AFDX-384 binding sites, respectively, are represented by M4MR and M2MR constitute only a minor portion. In cortex and hippocampus, 3H-AFDX-384 labels almost similar amounts of M2MR and M4MR alongside significant amounts of non-M2/non-M4MR. In cortex, the proportion of 3H-AFDX-384 binding sites attributable to M2MR can be increased by blocking M4MR with MT3 toxin without affecting non-M4MR. PD102807, which is considered as a highly selective M4MR antagonist failed to improve the discrimination of M2MR. Autoradiography with 3H-QNB showed genotype specific loss of binding sites. In conclusion: while 3H-pirenzepine showed the high selectivity towards M1MR, 3H-AFDX-384 binding sites represent different populations of MR subtypes in a brain-region-specific manner. This finding has to be taken into account when interpreting the binding data.